Sistem Informasi Penjualan LPG Pada PD. Sari Jaya Jakarta - Indah Kusuma Dewi - AMIK BSI Jakarta; Achmad Maezar Bayu Aji - STMIK Nusa Mandiri Jakarta (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2018)
ABSTRACT - PD. SARI JAYA is a company engaged in the sale. The system used is still using a manual data processing system where the data-data can be changed freely without any certainty of data. PD. SARI JAYA requires the existence of an innovation in the form of a system that is build and that support the service for the creation of a satisfaction that is perceived by employees and customers for that the author tries to make the final task on Sales System needed on PD. SARI JAYA which until now has not been computerized. At this time PD. SARI JAYA company which is engaged in